Culturally responsive teaching through primary science in Aotearoa New Zealand (UCL Press, 2024)
The need for better education through science is not a new idea in Aotearoa New Zealand. Through several curriculum changes, teachers have not been well supported by the Ministry of Education in how to implement these changes. In addition, since 2020, all classroom teachers are required to demonstrate how they are culturally responsive in their teaching practice, and what they are doing to be more culturally responsive year-on-year. Fortunately, a resource written by Māori teachers for teachers was launched in 2020 to help support teachers in being more culturally responsive. This article reports on how teachers are being supported to be more culturally responsive teachers by weaving together mainstream curriculum science and Mātauranga Māori (Indigenous traditional knowledge). It argues how mainstream curriculum and Mātauranga Māori can be partnered using a pūrākau (cultural narrative) in meaningful classroom practice. It concludes by showing how both mainstream and Māori pedagogies can work together to support all students' learning and cultural competence.